2015
DOI: 10.1186/s40543-015-0076-z
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antioxidant activity of methanol extracts of Arnebia benthamii (Wall ex. G. Don) Johnston—a critically endangered medicinal plant of North western Himalaya

Abstract: Background: Arnebia benthamii is one of the promising folklore medicinal plants which is being traditionally used over the years for the treatment of various prevailing diseases in the area. The aim of this research work was to evaluate the antimicrobial activity and antioxidant activity of methanolic plant extract. Methods: Antimicrobial activity of the plant extract (250-500 μg/ml concentration) was analyzed against Escherichia coli CD0006, Pseudomonas aeruginosa CD0023, Shigella flexneri CD0033, Klebsiella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…As known, in addition to the shikalkin derivatives, the A. euchroma root contains some new compounds [55]. The antimicrobial effect of A. euchroma has been reported in many previous studies [56,57]. Haghbeen et al [20] reported that A. euchroma root THF-extract grown in Iran showed antimicrobial activity (shikalkin pigment) and demonstrated that the highest control yield of the extract was obtained on M. luteus.…”
Section: Discussionmentioning
confidence: 95%
“…As known, in addition to the shikalkin derivatives, the A. euchroma root contains some new compounds [55]. The antimicrobial effect of A. euchroma has been reported in many previous studies [56,57]. Haghbeen et al [20] reported that A. euchroma root THF-extract grown in Iran showed antimicrobial activity (shikalkin pigment) and demonstrated that the highest control yield of the extract was obtained on M. luteus.…”
Section: Discussionmentioning
confidence: 95%
“…Researchers also investigated some derivatives of the Sh+ikonin component and their cytotoxic effect and antioxidant activity [ 290 , 291 ]. From the plant species the methanol extracted has antioxidant and antimicrobial effects, and hydroxyl radicals for DNA damage protection [ 292 ]. The phytochemicals existing in the Arnebiaeu chroma plant are utilized for treating carcinogenic diseases.…”
Section: Major Anticancer Agents Obtained From Medicinal Plantsmentioning
confidence: 99%
“…It is an alpine herb occurring at an altitude of 3500–4000 m, from Kashmir to Western Nepal, normally on open slopes with stony or rocky substrates. In Kashmir Valley, it is confined to certain areas such as Sinthon Top, Duksum, Karnah, Gurez, Lolab, Sonamarg, and Kargil and is rarely found [ 8 , 9 ]. It is classified as a critically endangered nonendemic plant of Kashmir [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…are reported to be traditional ayurvedic medicines for the treatment of diseases of the throat and tongue, fevers, and cardiac symptoms. The flowers are known to have a comforting effect on heart patients [ 11 ], while its roots have antiseptic and antibiotic properties [ 9 ]. Conservation of the existing germplasm of such a useful and threatened species is, therefore, a strategic need.…”
Section: Introductionmentioning
confidence: 99%